Pro iOS 5 augmented reality - Roche, Kyle (Apress, 2011)
Augmented reality takes the real world and through the use of graphics, sound and other effects allows you to enhance the environment. It makes a game more real. Your social media app puts you where want to be or go. Pro iOS 5 Augmented Reality walks you through the foundations of building an augmented reality application for the iPhone or iPad. From using MapKit, to the accelerometer and magnetometer, to integrating facial recognition and Facebook data, you'll learn the building blocks of creating augmented reality applications. Case studies are included in this one-of-a-kind book and you'll learn how to create augmented reality apps that unleash the full potential of the on-board sensors and camera. This book complements other iOS game or social media apps development books available from Apress. After reading Pro iOS 5 Augmented Reality, you'll be able to build augmented reality rich media apps or integrate all the best augmented reality techniques and tools into your existing apps.